Etude et restauration d'un relief en plâtre pour un des pilastres de la Porte de l'Enfer d'Auguste Rodin, musée Rodin - Juliette Robin Dupire (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The historical and technical studies of the relief allowed to replace that original cast in a larger context of creation of Rodin's Gate of Hell. Research was necessary to understand alterations such as blistering, lifting and deformation of the first layer of plaster. Treatments had to be adapted to the damaged plaster. The particularities related to the fragility and the minimal use of water that was required, had requested specific treatments for the structural reassembling, surface consolidation and cleaning methods.